The Dynamics of FDI Inflows, Economic Growth, Trade Openness and CO2 Emissions in India: An ARDL Approach with Structural Breaks - Manickam, Tamilselvan; Vijayakumar, N. C.; Kumar, G. Sathis; Pazhamalai, Srinivasan; Babu, S. Ravindra (International Journal of Energy Economics and Policy, 2025)
The present study empirically investigates the causal relationship among FDI inflows, economic growth, trade openness, and CO2 emissions in India from 1980 to 2023, employing the autoregressive distributed lag (ARDL) approach. Unlike previous studies, the structural breakpoints are identified in the time-series data using the multiple breakpoint test to incorporate into the ARDL model. The cointegration test shows a significant long-term relationship between the variables. The error correction model with structural breaks reveals a bidirectional causation between the FDI inflows and trade openness, validating the long-term complementary relationship. However, there is no significant evidence of causation between FDI inflows and economic growth in the long run. Besides, the FDI-Growth nexus is bidirectional in the short run, with the impact of FDI on GDP growth being relatively modest. While GDP and trade contribute to CO2 emissions, the study indicates no significant relationship between FDI inflows and CO2 emissions in both the long and short run. The findings do not support the pollution haven hypothesis in the Indian economy. The study emphasizes the establishment of future-ready infrastructure for the green FDI inflows, rather than the FDI that primarily focuses on generating employment opportunities in the economy.